'#OkBoomer, time to meet the Zoomers': studying the memefication of intergenerational politics on TikTok. Issue 16 (10th December 2021) - Zeng, Jing; Abidin, Crystal
ABSTRACT: TikTok, a short video platform featuring content between 15 and 60 seconds long, has become a popular and rapidly growing social media application around the world. As a platform catering for light entertainment, TikTok champions virality and encourages memetic remixes. Meme videos, mostly featuring lip-syncs, dance routines, and skits, have become one of the defining features of the platform. These seemingly trivial videos have been utilised by young TikTokers to advocate for various causes. This paper uses #OkBoomer memes as a case study to examine the political culture of young people and Gen Z in particular. By analysing how intergenerational politics has been 'memefied ', this study delineates how Gen Z imagines and expresses a generational sentiment towards 'Boomers' as the imagined other. They do so through short video cultures and practices on TikTok, drawing upon the networked experiences of their peers. Specifically, the paper considers the key controversial issues, meme forms and meme functions across the #OkBoomer memes on TikTok, and its eventual mainstreaming in society.